Battle hymn of the tiger mother - Chua, Amy. (New York : Penguin Books, 2011)
Traces the rewards and pitfalls of a Chinese mother's exercise in extreme parenting, describing the exacting standards applied to grades, music lessons, and avoidance of Western cultural practices.
This edition with a new afterword published in Penguin Books 2011.
Includes bibliographical references (p. 267-269).
Keywords: Chua, Amy; Chinese American women -- Biography; East and West -- Biography; Mothers -- United States -- Biography; Mothers and daughters -- China; Mothers and daughters -- United States